Primary Hepatic Leiomyosarcoma: a Case Report and Review of the Literature - Feretis, Themistoklis; Kostakis, Ioannis D; Damaskos, Christos; Garmpis, Nikolaos; Mantas, Dimitrios; Nonni, Afroditi; Kouraklis, Gregory; Dimitroulis, Dimitrios (Acta medica (Hradec Kralove), 2018)
BACKGROUND/AIM: Primary hepatic leiomyosarcoma is an extremely rare type of liver sarcoma with relatively poor prognosis, with about 50 cases having been reported in the literature. Potential origins of this tumor in the liver are the smooth muscle cells in the round ligament, intrahepatic blood vessels and intrahepatic bile ducts. There is no apparent sex predilection and there is a wide age range. The clinical presentation is not specific and the diagnosis depends on the expression of markers such as smooth muscle actin, desmin and vimentin by tumor cells. PATIENTS AND METHODS: Herein, we present a case of a bulky primary hepatic leiomyosarcoma in a 68-year-old female patient. The patient underwent resection of the exophytic mass en block with the hepatic segments III and IVB. CONCLUSION: Surgical resection is the most effective among the treatment options.
Keywords: počítačová rentgenová tomografie; Magnetic Resonance Imaging; nádory jater; leiomyosarcoma; Leiomyosarcoma; fatální výsledek; magnetická rezonanční tomografie; Humans; Chemotherapy, Adjuvant; hepatic; Female; Aged; liver; senioři; lidé; Liver Neoplasms; adjuvantní chemoterapie; primary; ženské pohlaví; Tomography, X-Ray Computed; Fatal Outcome; leiomyosarkom